2010
DOI: 10.1371/journal.pone.0011700
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Associated Macrophages Protect Colon Cancer Cells from TRAIL-Induced Apoptosis through IL-1β- Dependent Stabilization of Snail in Tumor Cells

Abstract: BackgroundWe recently reported that colon tumor cells stimulate macrophages to release IL-1β, which in turn inactivates GSK3β and enhances Wnt signaling in colon cancer cells, generating a self-amplifying loop that promotes the growth of tumor cells.Principal FindingsHere we describe that macrophages protect HCT116 and Hke-3 colon cancer cells from TRAIL-induced apoptosis. Inactivation of IL-1β by neutralizing IL-1β antibody, or silencing of IL-1β in macrophages inhibited their ability to counter TRAIL-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 58 publications
8
64
0
Order By: Relevance
“…A previous study demonstrated the crucial role of SNAIL in the resistance of tumor cells to TRAIL (41). As a downstream target of TRAIL, many factors acted on this role of SNAIL.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study demonstrated the crucial role of SNAIL in the resistance of tumor cells to TRAIL (41). As a downstream target of TRAIL, many factors acted on this role of SNAIL.…”
Section: Discussionmentioning
confidence: 98%
“…A positive feedback loop has been identified between tumor cells and macrophages that propagates the growth and promotes the survival of colon cancer cells: tumor cells stimulate macrophages to secrete IL-1β, which in turn, promotes Wnt signaling and stabilizes Snail in tumor cells, conferring resistance to TRAIL [26]. Furthermore, IL-1β and TAMs activate NF-κB-dependent PDK1/AKT signaling in tumor cells, and thereby inactivate GSK3β, enhance Wnt signaling and promote growth of colon cancer cells, suggesting another molecular link between inflammation and tumor growth [27].…”
Section: Tumor Associated Macrophagesmentioning
confidence: 99%
“…9 In terms of cell survival, Snail expression has been demonstrated to confer chemoresistance on breast, colon, lung, and pancreatic cancer cells. [10][11][12][13] Mechanistically, Snail can become stabilized and bind to PTEN promoter to repress its transcription during γ radiation-induced apoptosis. 14 It has also been documented that upon doxorubicin treatment, the pro-survival Akt pathway becomes activated to render breast cancer cells resistant to druginduced apoptosis.…”
Section: Introductionmentioning
confidence: 99%